La vida como radioteatro: estrategias metaficcionales en La tía Julia y el escribidor, de Mario Vargas Llosa - Cabrejo Cobián, José Carlos (2018)
Aunt Julia and the scriptwriter, novel written by Mario Vargas Llosa, is an emblematic work of metafiction, a type of fiction generally related to the fiction itself that reflects on its conventions and its construction modes, and plays with them. This analysis aims to address the metafictional strategies that articulate this novel, based on generative and tensive semiotics.